Impact of Transapical Aortic Cannulation for Acute Type A Aortic Dissection - Suenaga, Etsuro (Ann Thorac Cardiovasc Surg, 2015)
Objective: Early and mid-term result of transapical aortic (TAA) cannulation technique was evaluated compared with femoral artery (FA) cannulation in Acute Type A Aortic Dissection(AAAD). Methods: From January 2000 to October 2013, 80 consecutive patients with AAAD were underwent the ascending aortic replacement at Nagasaki Kouseikai Hospital. These patients were divided into two groups according to the cannulation site, FA cannulation (n = 34) and TAA cannulation (n = 46). Early and mid-term outcomes were compared between two groups. Result: Preoperative patient characteristics were almost comparable between groups. The time from skin incision to starting cardiopulmonary bypass (CPB) was significantly shorter in the TAA group (45 ± 16 vs 23 ± 5.1 min; P <0.001). There were no significant differences in post-operative cerebral infarction in two groups (17% versus 11%; P = NS). The operative mortality rate was 8.8% in FA group and 4.3% in TAA group (P = NS). During follow up (mean, 6.8 years), survival at 3 years and 5 years was 77.4% and 71.9% in TAA group and 76.3% and 73.8% in FA group, respectively. Conclusion: The postoperative morbidity and mortality between the two groups were almost the same. TAA cannulation for acute Type A aortic dissection is faster, easy and safe with acceptable early and mid-term outcome.